Turkish experience in rheumatoid arthritis patients with clinical apparent amyloid deposition. (December 2013) - Pamuk, Omer Nuri; Donmez, Salim; Pamuk, Gulsum Emel; Oz Puyan, Fulya; Keystone, Edward C.
Abstract Objectives: We evaluated the frequency of clinical apparent amyloid deposition, clinical features and outcome in our rheumatoid arthritis (RA) patients. Methods: Medical records of 1415 RA patients were examined. During routine follow-up, RA patients with proteinuria on urinalysis, underwent rectal biopsy. Results: Eleven patients (0.78%) were diagnosed with clinical apparent amyloid deposition. While the mean annual incidence of AA amyloidosis between 2001 and 2005 was 0.2%, it was 0.13% between 2006 and 2011. At initial presentation, three RA-related AA amyloidosis patients had nephrotic-range proteinuria and renal insufficiency, four had only nephrotic-range proteinuria, three had non-nephrotic-range proteinuria, and one had non-nephrotic-range proteinuria and renal insufficiency. The mean age in RA patients with AA amyloidosis was 60.8 years and disease duration was 12 years. Ten of 11 cases had positive rheumatoid factor. Two RA patients with AA amyloidosis who had been diagnosed in the pre-anti-TNF era died. Of the rest nine patients with AA amyloidosis, eight were administered anti-TNF therapy and one was given rituximab. In four patients, anti-TNF therapy led to disappearance of clinical features, decrement in proteinuria and resulted in improvement of or at least stabilization of renal functions. One patient using anti-TNF therapy died because of tuberculosis. One patient discontinued anti-TNF therapy and developed end-stage renal disease. Two patients have been started to be given anti-TNF therapy recently. In one patient who was given rituximab, there was regression of proteinuria and improvement in renal functions. Conclusions: We diagnosed a 0.78% frequency of AA amyloidosis in RA. It seems that – other than the risks of infection, tuberculosis – anti-TNF drugs seem to be effective on RA disease activity and also have renoprotective effects in RA patients with AA amyloidosis.